Appraisal of Basic Infrastructure in Primary Schools in Ijebu-Ode, Nigeria - Alaka, Chikodi; Ogunseye , Nathaniel (Journal of Architectural Research and Design Studies, 2026)
This study appraises the availability and level of decay of basic infrastructure in primary schools within Ijebu-Ode, Ogun State, Nigeria. Using a method of stratified random sampling, twenty private and public primary schools were selected. Data were collected through structured questionnaires, interviews, and direct observations. The data were analyzed using descriptive and inferential statistics. The results showed that most private schools are well managed and equipped, unlike the public schools, which have a high degree of inadequate basic infrastructure. This implies that private schools were more proactive in infrastructure management, ensuring regular maintenance and better resource allocation. The result of the ANOVA test revealed significant differences between the basic infrastructure availability of and its level of decay between public and private primary schools. The study concludes that the state of infrastructure in public primary schools poses serious challenges to effective teaching and learning. It therefore recommends a proactive approach, particularly preventive maintenance through collaborative effort.